2012
DOI: 10.1007/978-3-642-35176-1_32
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Sentiment Analysis of Twitter

Abstract: Abstract. Sentiment analysis over Twitter offer organisations a fast and effective way to monitor the publics' feelings towards their brand, business, directors, etc. A wide range of features and methods for training sentiment classifiers for Twitter datasets have been researched in recent years with varying results. In this paper, we introduce a novel approach of adding semantics as additional features into the training set for sentiment analysis. For each extracted entity (e.g. iPhone) from tweets, we add it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
243
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 388 publications
(252 citation statements)
references
References 6 publications
3
243
0
6
Order By: Relevance
“…In our previous work we showed that incorporating general conceptual semantics (e.g., "president", "company") into supervised classifiers improved sentiment accuracy [18]. SenticNet [8], 3 is a conceptbased lexicon for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work we showed that incorporating general conceptual semantics (e.g., "president", "company") into supervised classifiers improved sentiment accuracy [18]. SenticNet [8], 3 is a conceptbased lexicon for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
“…In this section we describe the addition of conceptual semantics into the SentiCircle representation. As in our previous work [18], AlchemyAPI 6 came first amongst the set of entity extractors we tested on Twitter. Here we use AlchemyAPI again to extract all named entities in tweets with their associated concepts.…”
Section: Enriching Senticircles With Conceptual Semanticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been argued that sentiment in text is not always associated with individual words, but instead, through relations and dependencies between words, which often formulate sentiment [16]. In previous work, these relations are usually complied as a set of syntactic patterns (i.e., Part-of-Speech patterns) [25,16,24], common sense concepts [6], semantic concepts [21,8], or statistical topics [20,11].…”
Section: Related Workmentioning
confidence: 99%
“…To extract the entities and their associated concepts in our datasets we use AlchemyAPI, 5 which we have previously evaluated its semantic extraction performance on Twitter data [21]. The number of extracted concepts in each dataset is listed in Table 3.…”
Section: Semantic Concept Featuresmentioning
confidence: 99%